Juridical Analysis of Legal Protection for Victims of Sexual Harassment Crime in the Perspective of Law Number 12 Year 2022 - Anasitas Nius Nifati Gulo; Van Lodewijk Purba; Jenriswandi Damanik (KOLABORASI: Journal of Multidisciplinary, 2024)
Sexual harassment is deviant behavior that forces a person to become the object of unwanted attention or sexual acts, either physically or verbally. Law Number 12 of 2022 on Sexual Violence Crimes (UU TPKS) regulates protection for victims, as stipulated in Articles 42 and 45, granting law enforcement and judges the authority to restrict the perpetrator’s movement to safeguard victims. The legal enforcement issues surrounding sexual harassment involve three key aspects: qualification of criminal acts, challenges in legal protection, and the effectiveness of victim protection. First, sexual harassment is an evolving crime, with an increasing number of victims each year, yet many victims still do not receive adequate legal protection. Second, the main challenge in ensuring legal protection lies in the suboptimal implementation of the UU TPKS, which aims to address law enforcement challenges, from prevention to victim recovery. Third, the UU TPKS provides a systemic protection framework for victims, including compensation-restitution, medical assistance, psychosocial rehabilitation, legal assistance, and an integrated criminal justice system that places victims as subjects in legal proceedings. To address these issues, the study adopts a library research method, examining legal literature, legislation, and expert theories related to penal policy and victim protection in sexual harassment cases. The findings affirm that the UU TPKS serves as a more comprehensive legal umbrella compared to the Indonesian Penal Code (KUHP) in safeguarding victims and prosecuting perpetrators of sexual harassment.